A new genus and species of micro-pagurid hermit crab (Crustacea, Decapoda, Paguridae) from the rariphotic reef zone in Curaçao, Lesser Antilles, Caribbean Sea - Lemaitre, Rafael; Felder, Darryl L. (Zootaxa, 2023)
During field investigations of deep-reefs off the coast of Curaçao in the Lesser Antilles, Caribbean Sea, a female specimen was collected of an undescribed micro-pagurid crab with striking dorso-ventral flattening of the right cheliped. It was further characterized by a reduced branchial formula, fourth pereopods with grasping-like spines instead of typically pagurid rasp-like scales, nearly symmetrical uropods and telson, and a minute pair of first pleopods (gonopods). The single specimen was discovered in samples from the rariphotic zone ( 130–309 m) obtained using a suction sampler operated from the manned submersible R/V Curasub over cryptic habitats and surfaces populated by communities of sessile macro-organisms. As the specimen does not fit any known pagurid taxon, we regard it to represent a new monotypic genus. We fully describe this new micro-pagurid as Raripagurus roseangelae n. gen., n. sp. and also provide photographs of its live coloration. The CO1 barcode for the holotype in the Barcode of Life Database and GenBank accession number are included as part of the description for any future phylogenetic investigations.